Transactional Sex: Supply and Demand Among European Men Who have Sex with Men (MSM) in the Context of Local Laws - Berg, Rigmor C. (Int J Sex Health, 2015)
Objectives: Transactional sex (TS) is generally defined as the trading of sex for material goods. Cast within the broader context of prostitution laws, we examined variations in the sociodemographic profile of men who have sex with men engaging in TS by payment direction (buying/selling). Methods: The data were collected as part of the 38-country European Men who have sex with men Internet Survey project, conducted in 2010. Results: About 12% of respondents reported engaging in TS in the past year. TS was associated with laws, age, education, employment, and residence. Conclusions: The striking sociodemographic differences in TS by payment direction suggest a power differential and a leading role of socioeconomic factors in TS.